Reduced levels of NADH-dependent glutamate dehydrogenase decrease the glutamate content of ripe tomato fruit but have no effect on green fruit or leaves - Ferraro, Gisela (2015)
Glutamate (Glu) is a taste enhancer that contributes to the characteristic flavour of foods. In fruit of tomato (Solanum lycopersicum L.), the Glu content increases dramatically during the ripening process, becoming the most abundant free amino acid when the fruit become red. There is also a concomitant increase in NADH-dependent glutamate dehydrogenase (GDH) activity during the ripening transition. This enzyme is located in the mitochondria and catalyses the reversible amination of 2-oxoglutarate to Glu. To investigate the potential effect of GDH on Glu metabolism, the abundance of GDH was altered by artificial microRNA technology. Efficient silencing of all the endogenous SlGDH genes was achieved, leading to a dramatic decrease in total GDH activity. This decrease in GDH activity did not lead to any clear morphological or metabolic phenotype in leaves or green fruit. However, red fruit on the transgenic plants showed markedly reduced levels of Glu and a large increase in aspartate, glucose and fructose content in comparison to wild-type fruit. These results suggest that GDH is involved in the synthesis of Glu in tomato fruit during the ripening processes. This contrasts with the biological role ascribed to GDH in many other tissues and species. Overall, these findings suggest that GDH has a major effect on the control of metabolic composition during tomato fruit ripening, but not at other stages of development.